Engineering Physiology Bases of Human Factors Engineering/ Ergonomics - Kroemer, Karl H. E.; Kroemer, Hiltrud J.; Kroemer-Elbert, Katrin E.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2010)
How big are people nowadays? How far can we reach? How strongly can we push our pull? How does our body develop muscle strength? What are our work capabilities? How can we measure and judge them? How can we design equipment and tasks to make work easy and effective? These and other information are available at the 4th edition of 'Engineering Physiology'. The text discusses, in practical terms, effects of environmental conditions and how shift work arrangements during day, evening, and night affect task performance. The 4th edition of 'Engineering Physiology' does not require extensive background knowledge from the reader, just interest - and it is interesting to read!
Skeletal Structures -- Muscles -- Neuromuscular Control -- Anthromechanics -- Respiration -- Circulation -- Metabolism -- Exercise and Work -- Thermal Environment -- Body Rhythms and Work Schedules -- Engineering Anthropometry.
Keywords: Engineering; Human physiology; Mechanical engineering; Biomedical engineering; Engineering; Biomedical Engineering; Human Physiology; Structural Mechanics